Co-implementing vitamin A supplementation with seasonal malaria chemoprevention in Sokoto State, Nigeria: a feasibility and acceptability study - Olusola Oresanya; Abimbola Phillips; Ekechi Okereke; Abraham Ahmadu; Taiwo Ibinaiye; Madeleine Marasciulo; Charlotte Ward; Olatunde Adesoro; Rilwanu Mohammed; Jamilu Nikau; Chris Osa Isokpunwu; Mohammad Ali Inname; et al. (BMC, 2022)
Abstract Background Bi-annual high dose vitamin A supplements administered to children aged 6-59 months can significantly reduce child mortality, but vitamin A supplementation (VAS) coverage is low in Nigeria. The World Health Organization recommends that VAS be integrated into other public health programmes which are aimed at improving child survival. Seasonal malaria chemoprevention (SMC) provides a ready platform for VAS integration to improve health outcomes. This study explored the feasibility and acceptability of integrating VAS with SMC in one local government area in Sokoto State. Methods A concurrent QUAN-QUAL mixed methods study was used to assess the feasibility and acceptability of co-implementing VAS with SMC in one LGA of Sokoto state. Existing SMC implementation tools and job aids were revised and SMC and VAS were delivered using a door-to-door approach. VAS and SMC coverage were subsequently assessed using questionnaires administered to 188 and 197 households at baseline and endline respectively. The qualitative component involved key informant interviews and focus group discussions with policymakers, programme officials and technical partners to explore feasibility and acceptability. Thematic analysis was carried out on the qualitative data. Results At endline, the proportion of children who received at least one dose of VAS in the last six months increased significantly from 2 to 59% (p < 0.001). There were no adverse effects on the coverage of SMC delivery with 70% eligible children reached at baseline, increasing to 76% (p = 0.412) at endline. There was no significant change (p = 0.264) in the quality of SMC, measured by proportion of children receiving their first dose as directly observed treatment (DOT), at baseline (54%) compared to endline (68%). The qualitative findings are presented as two overarching themes relating to feasibility and acceptability of the integrated VAS-SMC strategy, and within each, a series of sub-themes describe study participants' views of important considerations in implementing the strategy. Conclusion This study showed that it is feasible and acceptable to integrate VAS with SMC delivery in areas of high seasonal malaria transmission such as northern Nigeria, where SMC campaigns are implemented. SMC-VAS integrated campaigns can significantly increase vitamin A coverage but more research is required to demonstrate the feasibility of this integration in different settings and on a larger scale.